The Influence Of Knowledge, Skills, And Attitude On Career Development Opportunities In The Workplace - Prayogo, Dimas Ageng; Kosasih, Kosasih; Paramarta, Vip (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2024)
This research aims to analyze the influence of knowledge, skills, and attitudes on career development opportunities in the workplace.  In the era of globalization and increasingly fierce business competition, a deep understanding of the factors influencing career development becomes crucial for individuals and organizations. This research aims to explore the impact of knowledge, attitudes, and skills on the career development opportunities of working master's degree students in management at Universitas Sangga Buana YPKP Bandung.  The method used is quantitative, with a sample of 65 people selected through a non-probability purposive sampling technique.  Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression analysis techniques with the help of SPSS software. The analysis results show that knowledge, attitude, and skills significantly impact career development opportunities in the workplace.  This indicates that these variables strongly influence career development opportunities in the workplace.  Meanwhile, other variables are influenced by factors not studied in this research.  The higher a person's knowledge, skills, and attitudes, the greater the opportunities for career development in the workplace. This research provides new insights into the importance of knowledge and skills in enhancing career development opportunities in the workplace.  Attitude, although influential, requires a more in-depth approach to understand its impact.  The practical implication of these findings is the importance of training and development programs that focus on enhancing employees' knowledge and skills to support their career development.